Experience with use of three trocars and an adapted uterine manipulator in total laparoscopic hysterectomy - Portugal, Edward (2015)
Objective: To value the use of three 10 mm trocars and an adapted uterine manipulator in performing total laparoscopic hysterectomy (TLH). Design: Descriptive retrospective study. Setting: Gynecology and Obstetrics Service, Hospital III EsSalud, Puno, Peru. Participants: Patients with TLH indication. Interventions: In the period 2004-2010, total hysterectomy by laparoscopy was performed in 78 patients with TLH indication, using bipolar, monopolar y Liga Sure. Main outcome measures: Surgical technique evaluation, postoperative evaluation and complications. Results: From 78 operations programmed, two cases were converted to laparotomy due to vesical lesion and one due to tumor in broad ligament that prevented adequate access to the operative field. Average age was 41 to 45 years, hospitalization three days, and average duration of surgery 126 minutes. We had two cases of vesical lesions and one ureteral lesion. Conclusions: Three trocars TLH with adapted uterine manipulator is a safe procedure and technically feasible to be performed.